Cooperation and conflict across the major transitions - Davies, N (2016)
The history of life is punctuated by major transitions in individuality, when previously-independent biological units assemble into new agents. The stability of these evolutionary alliances is governed by the extent of cooperation and conflict among their constituents. In this thesis, I explore how ecology influences these social interactions. Part I investigates cooperation in arthropod societies. W. D. Hamilton's haplodiploidy hypothesis, which holds that asymmetries in sibling relatedness explain the exclusively-female worker caste of the social Hymenoptera, has fallen out of favour; instead, the preadaptation of females for rearing young is thought to explain who helps in these taxa. Analysing the evolution of paternal care, I show that this pattern of preadaptation is not itself a consequence of haplodiploidy inhibiting brood care by males. I then show how five key factors of sexual ecology—sex-specific preadaptation, labile sex allocation, sib-mating, promiscuity, and reproductive autonomy—have a major impact upon the evolution of sex-biased helping in arthropod societies. Finally, inclusive-fitness theory predicts that monogamy should promote worker sterility in insect societies, but a recent population-genetics model has challenged this prediction. I show that relaxing this model's genetic, evolutionary, and ecological assumptions supports inclusive-fitness theory. Part II investigates conflict within genomes. I show that transposons are under selection to drive their host populations extinct, and explore the transposon–host and transposon–transposon interactions that might prevent this outcome. While neither selection against transposons' deleterious effects nor exploitation by parasites can plausibly prevent extinction, I show that host suppression of transposons can; however, this is only stable in the long term if suppression makes transposition costlier. I conclude that complex life could not exist without the active suppression of genetic conflict. Overall, I argue that ecology explains patterns of cooperation and conflict across the major transitions.